Calculation of Life Insurance Premiums with Markov Chain Applications for Patients with Pulmonary Tuberculosis Disease in Indonesia - Putra, Fachrul Ananda; Purba, Daniel Victorio Rudolfo (Communication In Research And Publications, 2024)
This study aims to calculate the premium for Long Term Care (LTC) insurance on Annuity as A Rider Benefit products with a multi-status model. Pulmonary Tuberculosis is one of the major infectious diseases that contribute significantly to morbidity and mortality rates. Therefore, it is necessary to calculate insurance premiums that consider the health risks of sufferers. In this study, Markov chains are used to model the health status transition of individuals with Pulmonary Tuberculosis over time, considering several health states, such as healthy, sick, and dead. Tuberculosis epidemiological data in Indonesia is used to estimate the transition probabilities between health states. The case study used in this research is a 35-year-old man who participates in LTC insurance with a coverage period of 5 years. It is known that the value of compensation when a person dies is IDR 100,000,000. The interest rate used is 5%. The calculation results obtained annual premium for LTC insurance on Annuity as A Rider Benefit product is Rp294,333. Then the calculation of the annual net premium of this insurance is also calculated based on age and gender. When age increases, the premium will be greater, this is influenced by the greater chance of death when age increases. In addition, based on gender, it is found that the male premium is more expensive than the female gender. This is influenced by the chance of death of men is greater than women.